2017
DOI: 10.1021/acs.langmuir.6b03970
|View full text |Cite
|
Sign up to set email alerts
|

Unique Combination of Surface Energy and Lewis Acid–Base Characteristics of Superhydrophobic Cellulose Fibers

Abstract: Cellulose fibers were first functionalized on their surface by silanization with trichloromethylsilane in an optimized gas-solid reaction, and the occurrence of the reaction was assessed using attenuated total reflection Fourier transform infrared (ATR-FTIR) spectroscopy. Then, the changes in the physicochemical surface properties of the material were thoroughly assessed using inverse gas chromatography (IGC) and X-ray photoelectron spectroscopy as surface specific tools. A very surprising combination of resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…No previous studies of the surface of this type of materials by IGC were found in the literature. However, the γ s d values are comparable with those of chitosan or alginate alone or of other polysaccharides, such as cellulose and hemicelluloses . For instance, a 80% deacetylated chitosan presented a γ s d value of 46 mJ·m −2 at 50°C and sodium alginate showed a γ s d value of 39 mJ·m −2 at 25°C.…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…No previous studies of the surface of this type of materials by IGC were found in the literature. However, the γ s d values are comparable with those of chitosan or alginate alone or of other polysaccharides, such as cellulose and hemicelluloses . For instance, a 80% deacetylated chitosan presented a γ s d value of 46 mJ·m −2 at 50°C and sodium alginate showed a γ s d value of 39 mJ·m −2 at 25°C.…”
Section: Resultsmentioning
confidence: 78%
“…For instance, a 80% deacetylated chitosan presented a γ s d value of 46 mJ·m −2 at 50°C and sodium alginate showed a γ s d value of 39 mJ·m −2 at 25°C. A γ s d value of 42 mJ·m −2 was reported for bleached cellulose at 40°C and of 48 mJ·m −2 for xylan . These values reflect the major influence of the hydroxyl groups present along the chains of the PECs on the magnitude of the Lifshitz Van der Waals forces, which was determined based on measurements of the interactions of the materials with the n ‐alkanes (apolar probes).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…IGC is a very accurate and versatile characterization tool. In particular, IGC can overcome the contact angle measurement limitations in the analysis of porous, rough, and heterogeneous surfaces [ 6 , 7 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The low-temperature chemical vapor deposition (CVD) was utilized to the hydrophobic modification for the cellulose-based materials and wood composite materials. For example, Gamelas et al [ 24 ] implemented fast CVD to fabricate hydrophobic pulp by using trichloromethylsilane vapor silanization. Although this method could offer the hydrophobic function to the modified surfaces by the salinization treatment, the size of cellulose fibers was in the nanometer range.…”
Section: Introductionmentioning
confidence: 99%